2019
DOI: 10.3390/molecules24213889
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer and Ototoxicity Characteristics of the Curcuminoids, CLEFMA and EF24, in Combination with Cisplatin

Abstract: In this study, we investigated whether the curcuminoids, CLEFMA and EF24, improved cisplatin efficacy and reduced cisplatin ototoxicity. We used the lung cancer cell line, A549, to determine the effects of the curcuminoids and cisplatin on cell viability and several apoptotic signaling mechanisms. Cellular viability was measured using the MTT assay. A scratch assay was used to measure cell migration and fluorescent spectrophotometry to measure reactive oxygen species (ROS) production. Western blots and lumines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…The reported IC 50 value was 12 μM in A549 cells upon Cu(II) complex exposure [15] . When compared with the literature, IC 50 values for A549 cells were found to be 7.49 and 5.1 at the same treatment period used in this study, [23,24] showing the consistency of our findings. Moreover, the Cu(II) flavonoid complex we used in our study has lower IC 50 values than Cisplatin, which indicates that the complex has the potential to act as an effective metal‐based anticancer drug (Table 1).…”
Section: Resultssupporting
confidence: 87%
“…The reported IC 50 value was 12 μM in A549 cells upon Cu(II) complex exposure [15] . When compared with the literature, IC 50 values for A549 cells were found to be 7.49 and 5.1 at the same treatment period used in this study, [23,24] showing the consistency of our findings. Moreover, the Cu(II) flavonoid complex we used in our study has lower IC 50 values than Cisplatin, which indicates that the complex has the potential to act as an effective metal‐based anticancer drug (Table 1).…”
Section: Resultssupporting
confidence: 87%
“…For example, complex 4a showed relatively strong antiproliferative activities against the MDA-MB-231, 786-O, A549, and HepG2 cell lines with IC 50 values of 2.6, 3.7, 4.6, and 5.0 μM, respectively, whereas the IC 50 values for 4b were 14.4, 14.1, 7.5, and 24.1 μM. Meanwhile, cisplatin from the literatures 20–23 was used as a competitor, the IC 50 values of which against MDA-MB-231, 786-O, A549, and HepG2 cell lines were 7.8, 10.7, 9.8, and 15.9 μM, respectively, the results are presented in Table 1. Hence, the nitrogen mustard–conjugated terpyridine Ru complex exerted better antiproliferative activities than the corresponding Fe complex 4b and cisplatin.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that mechanotransducer (MET) channels mediate the entry of cisplatin into cochlear hair cells, but it remains unclear whether MET channels are blocked during that process. 30,46,53 A study using larval zebrafish confirmed that cisplatin-induced damage to the hair cells relies on functional MET channels. 19 Furthermore, the effect of platinum (II) complexes on adult zebrafish auditory system suggested that cisplatin, and to a limited extent phenanthriplatin, can induce hair cells loss in particular regions of the saccule but not the utricle, 56 suggesting either various regional susceptibility to cisplatin or its distinct diffusion or transport pattern.…”
Section: Discussionmentioning
confidence: 98%
“… 14 , 51 , 52 Cisplatin induces cytotoxicity by binding to the nuclear DNA, leading to apoptosis, particularly in the proliferating cells. 53 In addition to that, cisplatin can mediate the activation of NADPH oxidase 3 (NOX3), which catalyzes the production of superoxide, representing reactive oxygen species (ROS). Overproduction of ROS can activate the signal transducer and activator of transcription 1 (STAT1), inducing the inflammation.…”
Section: Discussionmentioning
confidence: 99%